2004
DOI: 10.1080/08958370490506600
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Activity of Ambient Particulate Matter in Macrophage Activity-Suppressed,N-Acetylcysteine-Treated, iNOS- and IL-4-Deficient Mice

Abstract: In previous studies, we have shown strong adjuvant activity for Ottawa dust (EHC-93) after coexposure of the BALB/c mouse to EHC-93 and ovalbumin. Mice were intranasally sensitized at days 0 and 14 with 200 microg ovalbumin and 150 microg EHC-93, and challenged with ovalbumin at days 35, 38, and 41 with 200 microg ovalbumin. Mice were autopsied at day 42. This adjuvant activity was shown for the antibody response to ovalbumin (immunoglobulins E, G1, and G2a), histopathological lesions in the lung, cytokines, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In this study, the 6-day exposure regimen of SAS, which was considered comparable to the 5-day exposure period as used previously (Arts et al, 2007), did not affect body weights; it induced transient changes in breathing parameters without other indications of distress, but it increased levels of ALP, GGT, LDH, and NAG, increased numbers of neutrophils and macrophages in BAL fluid, increased relative lung weight, and induced a mild granulomatous (neutrophilic) inflammation (Table 4). We used inhalation as a more physiological route of exposure than the intranasal, intratracheal, or intraperitoneal routes of administration used in several other studies studying the effects of coexposure or preexposure to particles in respiratory allergy (Lambert et al, 1999(Lambert et al, , 2000Ma & Ma, 2002;Steerenberg et al, 2003aSteerenberg et al, , 2003bSteerenberg et al, , 2004aSteerenberg et al, , 2004bSiegel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the 6-day exposure regimen of SAS, which was considered comparable to the 5-day exposure period as used previously (Arts et al, 2007), did not affect body weights; it induced transient changes in breathing parameters without other indications of distress, but it increased levels of ALP, GGT, LDH, and NAG, increased numbers of neutrophils and macrophages in BAL fluid, increased relative lung weight, and induced a mild granulomatous (neutrophilic) inflammation (Table 4). We used inhalation as a more physiological route of exposure than the intranasal, intratracheal, or intraperitoneal routes of administration used in several other studies studying the effects of coexposure or preexposure to particles in respiratory allergy (Lambert et al, 1999(Lambert et al, , 2000Ma & Ma, 2002;Steerenberg et al, 2003aSteerenberg et al, , 2003bSteerenberg et al, , 2004aSteerenberg et al, , 2004bSiegel et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, although particles may act as an adjuvant for allergic sensitization (Lambert et al, 1999(Lambert et al, , 2000Steerenberg et al, 1999Steerenberg et al, , 2003aSteerenberg et al, , 2003bSteerenberg et al, , 2004aSteerenberg et al, , 2004bSteerenberg et al, , 2005Hamada et al, 2000;Ma & Ma, 2002;Siegel et al, 2004;Dong et al, 2005a), this is a delayed 936 J. H. E. ARTS ET AL. response and does not explain acute particle effects on airway hyperreactivity during episodes of high air pollution.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The toxic particles and gases may singly or in combination have a multitude of effects including reducing mucociliary clearance [49], decreasing alveolar macrophage function [50], diminishing production of antiviral defenses [13] as well as having more broad systemic immuntoxicity affecting both the myeloid and lymphatic systems [10]. Recently we demonstrated that exposure to DE decreased expression and production of host defense molecules including surfactant protein A (SP-A), SP-D, and clara cell secretory protein (CCSP) [51], and this was associated with increased proliferation of influenza virus in both in vitro [52] and vivo systems [13,53-55].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NAC pretreatment was correlated with the downregulation of inflammatory markers. Steerenberg et al (2004) used mice with natural resistance-associated macrophage protein activity, with NAC pre-treatment, deficient inducible nitric oxide synthase, and deficient IL-4 expression, which were co-exposed to OVA and Ottawa dust. This experiment showed no differences in histological inflammation or immunoglobulin formation.…”
Section: Resultsmentioning
confidence: 99%